2020
DOI: 10.1063/5.0003333
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-electrolyte solvation and reaction in the electrolyte of a lithium ion battery: A ReaxFF reactive force field study

Abstract: In the electrode/electrolyte interface of a typical lithium-ion battery, a solid electrolyte interphase layer is formed as a result of electrolyte decomposition during the initial charge/discharge cycles. Electron leakage from the anode to the electrolyte reduces the Li+-ion and makes it more reactive, resulting in decomposition of the organic electrolyte. To study the Li-electrolyte solvation, solvent exchange, and subsequent solvent decomposition reactions at the anode/electrolyte interface, we have extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Similar as in hybrid MD/MC schemes (see below), the charge state of the lithium atoms can be altered in MC steps. [ 176 ] This is similar in spirit to simulations of a model battery cell without an explicit treatment of electron particles. [ 177 ] ML models that can universally track electron density and its transfer and modulation for large scale reactive simulations can usher in a new era (see Section 4.1).…”
Section: State‐of‐the‐art In Sei Modellingmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar as in hybrid MD/MC schemes (see below), the charge state of the lithium atoms can be altered in MC steps. [ 176 ] This is similar in spirit to simulations of a model battery cell without an explicit treatment of electron particles. [ 177 ] ML models that can universally track electron density and its transfer and modulation for large scale reactive simulations can usher in a new era (see Section 4.1).…”
Section: State‐of‐the‐art In Sei Modellingmentioning
confidence: 82%
“…Indeed, this framework could successfully describe the reduction of EC as well as the cascade of consecutive reactions [ 146 ] (left snapshot in Figure 3d), although these decomposition mechanisms have to be carefully parametrized. [ 176 ] Notably, the latter work revealed a notable impact of the lithium ion solvation shell on the EC degradation. Furthermore, the authors suggest to use two different parameter sets—one for metallic lithium and one for lithium ions—to incorporate distinct oxidation states.…”
Section: State‐of‐the‐art In Sei Modellingmentioning
confidence: 94%
“…Given such findings, it is not surprising that continuous efforts during decades have been devoted to the development of polarisable and advanced force‐fields for application in the battery context, as exemplified here by a recent battery‐related interface study regarding solvent decomposition reactions at the anode/electrolyte interface using (≤2.5 ns) long MD simulations with the ReaxFF polarizable force field. [ 30 ] The considerable efforts spent in the literature on the development of polarizable interaction models for complex energy materials applications reflects both the great need for efficient force fields that allow large‐scale, long‐time computer simulations and the formidable challenge that it constitutes to generate force fields that accurately capture the electronic effects.…”
Section: Toward Inverse Design Of Battery Interfacesmentioning
confidence: 99%
“…The ReaxFF method has been extensively applied in battery applications, especially in the areas of anode/electrolyte interfaces [15], electrolytes [16][17][18], and cathode/electrolyte interfaces [19,20]. However, no ReaxFF study has been reported on the current collector/electrode interface.…”
Section: Introductionmentioning
confidence: 99%